Kualifikasi Pelaku Tindak Pidana Pengrusakan Barang yang Dilakukan Secara Bersama-Sama - Mei Indah Ngilyaubun; Juanrico Alfaromona Sumarezs Titahelu; Jacob Hattu (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The current crimes encountered are crimes committed jointly or with participation (deelneming).Purposes of the Research: The purpose of the study is to analyze and discuss how the qualifications of each actor in the crime of destroying other people's property are carried out together and to analyze and discuss how the form of accountability of the perpetrators of the criminal act of destroying other people's property is carried out together.Methods of the Research: This method of research in writing uses a type of normative juridical research that examines positive legal provisions, legal principles, and legal doctrines, using approaches: statute approach and conceptual approach. The technique of collecting legal materials through literature studies and legal material analysis techniques in this study uses qualitative analysis techniques.Results of the Research: Based on the results of the research, the qualifications of each defendant are not the same, namely the defendant Helmi Untarola who has acted as an advocate (uitlokker) as well as a perpetrator (pleger) in the crime. Then there were 3 (three) other defendants, namely the defendant Ayub Marshel Balubun, the defendant Frangky Wakim, and the defendant Marten Wakim who had followed the advice of the defendant Helmi Untarola. Defendant I Helmy Untarola Defendant II Ayub Marshel Balubun, Defendant III Franky Wakim, and Defendant IV Marten Wakim were proven legally to have committed a criminal act of